The Effect of Digital Marketing and Digital Administration Policies on Patient Retention through Health Service Satisfaction at Advent Hospital Manado - Mawa, Melissa Abigael C; Niode , Nurdjannah J; Umboh , Adrian (Science Tech Group, 2026)
The rapid digital transformation in healthcare has driven hospitals to adopt digital marketing and digital administration policies to improve patient satisfaction and retention. However, empirical evidence on the mechanisms linking these policies to patient retention remains limited, particularly in Indonesian private hospitals. This study examines the effects of digital marketing and digital administration policies on patient retention, with healthcare service satisfaction as a mediating variable, at Advent Hospital Manado. A quantitative cross-sectional survey was conducted using a structured questionnaire, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with all constructs specified as reflective. The respondents were predominantly female, with two dominant age groups (25–35 years and >55 years), indicating different digital behavior patterns. Facebook was identified as the main referral platform, reflecting its effectiveness in reaching adult and elderly patients. Overall, respondents reported high and homogeneous perceptions of digital services, suggesting positive evaluations, although a potential ceiling effect should be considered. The findings indicate that digital marketing and digital administration policies positively influence patient satisfaction, which in turn enhances patient retention. Demographic characteristics and digital literacy shape patient perceptions, highlighting the importance of optimizing digital platforms and administrative processes to strengthen long-term patient retention. This study contributes to the achievement of Sustainable Development Goal (SDG) 3 by highlighting how digital healthcare strategies enhance patient satisfaction and continuity of care, thereby promoting healthy lives and well-being. In addition, the findings support SDG 9 by demonstrating the role of digital marketing and digital administrative innovations in strengthening resilient healthcare service infrastructure and fostering innovation within private hospitals.